2018
DOI: 10.1007/s10815-018-1214-5
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis does not affect live birth rates of patients submitted to assisted reproduction techniques: analysis of the Latin American Network Registry database from 1995 to 2011

Abstract: Our results demonstrate that endometriosis does not affect the outcome of patients subjected to IVF/ICSI and although patients with endometriosis present lower number of oocytes and higher cancelation rate, these shortcomings do not reduce pregnancy and live birth rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 21 publications
0
9
0
2
Order By: Relevance
“…The symptoms include dysmenorrhea, dyspareunia, and chronic pelvic pain, which are typically present during the reproductive years (3,4). The prevalence of endometriosis in reproductive-age women is estimated to be 5% to 15%, and 30% to 50% in women with infertility (5)(6)(7). Assisted reproductive technology (ART) can be used to help women achieve pregnancy; however, some studies have suggested that women with endometriosis have worse laboratory and clinical outcomes compared with other patients undergoing in vitro fertilization (IVF) (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The symptoms include dysmenorrhea, dyspareunia, and chronic pelvic pain, which are typically present during the reproductive years (3,4). The prevalence of endometriosis in reproductive-age women is estimated to be 5% to 15%, and 30% to 50% in women with infertility (5)(6)(7). Assisted reproductive technology (ART) can be used to help women achieve pregnancy; however, some studies have suggested that women with endometriosis have worse laboratory and clinical outcomes compared with other patients undergoing in vitro fertilization (IVF) (8).…”
mentioning
confidence: 99%
“…Other investigators have attempted to uncover endometrial factors that could alter endometrial receptivity or disrupt estrogen and progesterone signaling to result in implantation failure among patients with endometriosis (12,13). Lower implantation and clinical pregnancy rates in patients with endometriosis have been observed in several clinical studies, but the findings are conflicting (2,4,6,14). Implantation and pregnancy outcomes among patients with endometriosis may also vary by the cycle type (i.e., fresh versus frozen embryo transfer).…”
mentioning
confidence: 99%
“…Realizando a análise dividindo estes grupos por faixa etária, os resultados foram semelhantes, mostrando que a taxa de gravidez e a taxa de nascidos vivos foram iguais na comparação entre os grupos. (MURTA M et al, 2018) Ademais, o estudo de caso controle realizado no Centro de Pesquisa em Biomedicina Reprodutiva do Instituto Royan em Teerã, Irã, de abril de 2013 a dezembro de 2014, corrobora para os dados apresentados pelo estudo acima. Neste os resultados revelam que a existência de endometriose por si só não tem efeito nas taxas clínicas de gravidez e nascidos vivos, entretanto, a presença de endometriose infiltrada mostra reduções nas taxas expostas (ASHRAFI M et al, 2018).…”
Section: Resultsunclassified
“…Nesse contexto, expõe-se que tanto a Brazilian Journal of Health Review, Curitiba, v.4, n.2, p. 4524-4536 mar./apr. 2021 infertilidade causada diretamente pela endometriose, quanto a infertilidade causada por fator inexplicado ou fator tubário, apresentam mesmo desempenho quando submetidas a Fertilização in vitro/injeção intracitoplasmática de espermatozoides (FIV/ICSI) (MURTA M et al, 2018;OZGUR K et al, 2016)).…”
Section: Discussionunclassified
“…For the regeneration and repair of endometrial injury, the traditional treatment mainly includes surgical treatment, intrauterine barrier, endocrine therapy, increasing endometrial blood perfusion, and so on. 6 , 7 However, the methods to promote endometrial regeneration after the moderate and severe injury are still very limited, which could not avoid endometrial regeneration disturbance and postoperative adhesion recurrence. Therefore, the key to successful treatment is the ability to prevent the reformation of uterine adhesion and promote the regeneration and repair of endometrium.…”
Section: Introductionmentioning
confidence: 99%